Phytosociological Study of Navegaon National Park (Maharashtra) - Ilorkar, V. M.; Khatri, P. K. (Indian Forester, 2003)
Vegetation studies were conducted in the Navegaon National Park in order to assess the floristic composition. The forest is composed of 40 species of trees, 16 species of shruhs and 44 species of herbs. Three plant communities were identified, namely (1) Tectona-PterocarpusBuchanania, (2) Cleistanthus-Ougeinia-Tectona, and (3) Cleistanthus-Lagerstroemia-Terminalia; corresponding to three elevational ranges, i.e. 300-400m, 400-500m and 500-600m, respectively. Cleistanthus collin us is the most dominant species with density 3711ha followed by Tectona grandis 175/ha. Biotic disturbances were observed at lower elevation which has resulted in the absence of Raunkiaer’s normal frequency distribution. Measures are suggested to restore the density and protect the ecosystem.